Comprehensive Analysis of PTEN Alterations in Prostate Cancer: A cBioportal Study - ogbonnaya, Chidozie; Ononuju, Uzochukwu Alozie (International Journal of Innovative Research in Medical Science, 2023)
Prostate cancer (PCa), a leading cause of cancer-related mortality among men, demands an intricate understanding of its molecular landscape for improved diagnostics and treatment strategies. This study investigates the prevalence and clinical significance of Phosphatase and tensin homolog (PTEN) alterations in prostate cancer using data sourced from cBioportal. Analysing 10,998 samples across 26 prostate cancer studies, our findings reveal that PTEN alterations occur in 19% of patients, with deep deletion (PTEN HOMODELETED) being the most significant genetic alteration. Notably, Metastatic Prostate Adenocarcinoma exhibits the highest prevalence of PTEN mutations, while Prostate Adenocarcinoma Organoids show the least. Correlation analyses unveil associations between PTEN deep deletion and age, particularly within the 42-72 age range, as well as with Pelvic Radiation Disease Local Treatment at Diagnosis and primary Sample Type. Survival analysis indicates a significantly lower median overall survival in months (95% CI) for patients with PTEN alterations (96.00 months, 95% CI: 65.36 - 113.98) compared to unaltered cases (120.0 months, 95% CI: 115.05 - 160.00), highlighting the clinical relevance of PTEN in PCa and its correlation with disease progression and remission. The study concludes by discussing the potential implications of these findings, recognizing limitations, and emphasizing the critical need for targeted therapeutic strategies based on PTEN status in PCa management.